Infant spinal anesthesia: Do girls need a larger dose of local anesthetic?. Issue 10 (17th August 2017) - Frawley, Geoff; Huque, Md Hamidul
Summary: Background: Gender differences in absorption, distribution, and metabolism of a number of anesthetic agents have been identified in adults. Clinically, adult studies suggest women demonstrate slower onset of opioid analgesic effects, lower spinal and epidural dose requirements, and greater sensitivity to neuromuscular blocking agents. Sex‐related differences in the pharmacokinetics and pharmacodynamics of local anesthetics in neonates and infants, however, have not been well documented. As a result, it is not known whether modification of the dose of local anesthetic for awake spinal anesthesia in infants is required. Aims: Our aim was to determine whether the ED50 and ED95 of local anesthetics used for infant spinal anesthesia are different between sexes. Methods: This was a retrospective analysis of data previously collected during dose‐response studies of levobupivacaine and ropivacaine spinal anesthetics. The doses were reanalyzed using generalized linear regression analysis to determine whether there is a discernible difference in dose requirements between male and female infants. Results: One hundred and twenty infant spinal anesthetics were reviewed. For levobupivacaine, the ED50 (95% CI) was 0.69 (0.49‐0.88) mg vs 0.49 (0.33‐0.65), whereas the ED95 (95% CI) was 1.07 (0.73‐1.41) vs 0.93 (0.64‐1.22) for girls and boys, respectively. [Correction added on 20 October 2017 after first online publication: ED50 of levobupivacaine has been interchanged from '0.49 (0.33–0.65) mg vs 0.69 (0.49–0.88)' to '0.69 (0.49–0.88) mg vs 0.49 (0.33–0.65)' at the request of the author]. For ropivacaine spinal anesthesia, the ED50 (95% CI) was 0.64 (0.35‐0.92) mg vs 0.30 (−0.32‐0.92), whereas the ED95 (95% CI) was 1.30 (0.73‐1.87) vs 1.66 (0.55‐2.76) for girls and boys, respectively. Conclusion: There is no evidence that sex differences occur at the ED50 dose range or at the clinically relevant ED95 dose. Modification of spinal anesthetic dose is not required for infant girls.